Evaluation of operation swordfish: a near-repeat target-hardening strategy - Johnson, Shane D. (Journal of experimental criminology, 2017)
This paper reports an evaluation of a police-led target-hardening crime prevention strategy inspired by research concerned with space-time patterns of burglary.